THE LEGAL CONSTRUCTION OF LICENSING AND SUPERVISION OF SHARIA MULTILEVEL MARKETING IN INDONESIAN TRADE LAW - Tri Hidayati; Masyithah Umar; Fathurrahman Azhari; Mujiburohman Abul Abas (Fakultas Syariah, 2022)
Trade law in Indonesia has not accommodated Sharia Multilevel Marketing (Sharia MLM). The legitimacy of the Sharia status and supervision by the the National Sharia Council of the Indonesian Ulema Council (DSN MUI) does not have legal implications for the legality of the Sharia MLM company business entity. This article aims to explain the urgency of Sharia MLM regulation in trade law and provide input on the legal construction of licensing and supervision of Sharia MLM to maximize the achievement of trade law in Indonesia. This normative legal research uses statutory and conceptual approaches with a legal construction method. The legal materials were analyzed usingcontent analysis technique and prescriptive methodology. The results show that the legal construction of Sharia MLM in trade law is urgently carried out by the government using an integration-partnership model between DSN MUI and the Indonesian Ministry of Trade in the licensing and supervision system of Sharia MLM. The application of this model can legitimize the legal status of a Sharia MLM company so that it can become a locomotive for accelerating the Islamic economic ecosystem to advance the national economy.Hukum perdagangan di Indonesia belum mengakomodasi Multilevel Marketing Syariah (MLM Syariah). Legitimasi status Syariah dan pengawasan oleh Dewa Syariah Nasional Majelis Ulama Indonesia (DSN MUI) tidak berimplikasi hukum terhadap status hukum badan usaha perseroan MLM Syariah. Artikel ini bertujuan menjelaskan urgensi pengaturan MLM Syariah dalam hukum perdagangan dan memberikan masukan konstruksi hukum perizinan dan pengawasan MLM Syariah dalam rangka memaksimalkan tercapainya tujuan hukum perdagangan di Indonesia. Penelitian hukum normatif ini menggunakan pendekatan perundang-undangan dan pendekatan konseptual dengan metode konstruksi hukum. Bahan hukum dianalisis menggunakan teknik content analysis dan metode preskriptif. Hasil penelitian menunjukkan bahwa konstruksi hukum MLM Syariah dalam hukum perdagangan urgen dilakukan pemerintah dengan menggunakan model integrasi-kemitraan antara DSN MUI dan Kementerian Perdagangan dalam sistem perizinan dan pengawasan MLM Syariah. Penerapan model ini dapat melegitimasi status hukum perseroan MLM Syariah sehingga dapat menjadi lokomotif akselerasi ekosistem ekonomi Islam untuk memajukan perekonomian nasional.